Chemical signalling in lizards: an interspecific comparison of femoral pore numbers in Lacertidae. (24th October 2014) - Baeckens, Simon; Edwards, Shelley; Huyghe, Katleen; Van Damme, Raoul
<x xml:space="preserve">Abstract</x> Animals communicate via a variety of sensory channels and signals. Studies on acoustic and visual communication systems suggest that differences in the physical environment contribute to the variety of signalling behaviour, with species investing in those signals that are transmitted best under the local conditions. Whether or not environmental tuning also occurs in chemical communication systems has received much less attention. In the present study, we examined the effect of several aspects of the physical environment on the chemical communication system of lacertid lizards (family Lacertidae). The numbers of femoral pores are used as a proxy reflecting how much a particular species invests in and relies upon chemical signalling. Femoral pores are specialized epidermal structures that function as a secretion channel for the waxy substance produced by glands. In some lacertid species, the secretion carries infochemicals that play an important role in social communication. The number of femoral pores varies considerably among species. We have compiled data on femoral pore numbers for 162 species and tested for the effects of climate and substrate use. After correcting for body size and taking the phylogenetic relationships among the species into account, we found no effect of climate conditions or latitude on species pore numbers. Substrate use did affect pore numbers: shrub‐climbing species tended to have fewer femoral pores than species inhabiting other substrates. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 114, 44–57.